Genetic risk factors in Finnish patients with Parkinson's disease - Ylönen, Susanna; Siitonen, Ari; Nalls, Michael A.; Ylikotila, Pauli; Autere, Jaana; Eerola-Rautio, Johanna; Gibbs, Raphael; Hiltunen, Mikko; Tienari, Pentti J.; Soininen, Hilkka; Singleton, Andrew B.; Majamaa, Kari (Parkinsonism & related disorders, 2017)
Variation contributing to the risk of Parkinson's disease (PD) has been identified in several genes and at several loci including GBA, SMPD1, LRRK2, POLG1, CHCHD10 and MAPT, but the frequencies of risk variants seem to vary according to ethnic background. Our aim was to analyze how variation in these genes contributes to PD in the Finnish population. The subjects consisted of 527 Finnish patients with early-onset PD, 325 patients with late-onset PD and 403 population controls. We screened for known genetic risk variants in GBA, SMPD1, LRRK2, POLG1, CHCHD10 and MAPT. In addition, DNA from 225 patients with early-onset Parkinson's disease was subjected to whole exome sequencing (WES). We detected a significant difference in the length variation of the CAG repeat in POLG1 between patients with early-onset PD compared to controls. The p.N370S and p.L444P variants in GBA contributed to a relative risk of 3.8 in early-onset PD and 2.5 in late-onset PD. WES revealed five variants in LRRK2 and SMPD1 that were found in the patients but not in the Finnish ExAC sequences. These are possible risk variants that require further confirmation. The p.G2019S variant in LRRK2, common in North African Arabs and Ashkenazi Jews, was not detected in any of the 849 PD patients. The POLG1 CAG repeat length variation and the GBA p.L444P variant are associated with PD in the Finnish population. •We screened Finnish Parkinson's disease patients for known genetic variants.•The POLG1 CAG length variation is associated with Parkinson's disease in Finland.•The GBA p.L444P is a risk factor for Parkinson's disease in Finland.•Whole exome sequencing revealed five variants that were not found in controls.